Enhanced charge balance in QLEDs using oxygen vacancy induced defect states in Nb2O5 interfacial layer - Choi, Min Jung; Yun, Jung Min; Bin Kim, Yu; Kim, Seunghwan; Park, Soohyung; Kang, Seong Jun (The Korean Physical Society, 2025)
To enhance the performance of quantum-dot light emitting diodes (QLEDs), we used an Nb2O5 interfacial layer as a buffer layer. The Nb2O5 layer is used as an n-type semiconductor with electron transport properties. In this study, a significant number of defect states resulting from the oxygen vacancies in the Nb2O5 layer were used to create gap states, bringing the valence band maximum (VBM) energy level closer to the Fermi level. This resulted in a lower injection barrier, facilitating efficient hole transport. However, charge imbalance occurs due to electron accumulation in the emission layer, resulting from the mobility difference between electrons and holes. This issue can be resolved by using the Nb2O5 interfacial layer, leading to a current efficiency of 10.1 cd/A, the luminance of 106,194 cd/m2, and the EQE of 2.4 %. This represents almost a two-fold performance improvement compared to QLEDs device without the Nb2O5 interfacial layer. These results demonstrate that the ITO/Nb2O5/ V2O5/TFB/QDs/ZnO/Al structure of the device can enhance the performance of QLEDs by facilitating efficient hole transport through oxygen vacancies.